O trabalho docente no Instituto Federal de Educação, Ciência e Tecnologia: a subjetividade entre o desgaste mental e o adoecimento psíquico - Silva, Alline Santos (2020)
This research aims to identify, analyze and understand how (professors or faculty members) subjectify psychological distress and illness at work, apprehending how these workers make sense of their reality. For that, the metamorphoses of the world of work were high lighted, allied to the process of expansion of the professional, scientific and technological education network and its consequences on the organization of teaching work in the Federal Institutes of Education, Science and Technology (IFs). Thus, the processes to treat suffering and mental distress and other forms of mental illness resulting from the work of teachers in professional, scientific and technological education based on Historical-Dialectical Materialism and through the mediations of Social Psychology at Work were researched. This basic qualitative research is aimed at understanding the relationships between the kind of work, teaching work, the conditions under which this work develops and the health-illness-work process. Permanent teaching staff at the Federal Institute of Education, Science and Technology of Goiás (IFG) were interviewed. The analysis of documents and legislation was also used to complement the collection of data. And also, the data triangulation was development between the categories of analysis and the interviews. The research identified the existence of several studies that address teaching workers in the public school system. However, within the scope of the Federal Institutes, the number of studies is still not significant, especially concerning the area of knowledge of Psychology focused on Occupational Health. In addition, there may be negative consequences for the social group and for the subject, such as suffering, worsening conflicts and increasing the probabilities of illness, especially psychic.